Silicon-based negative electrode material, preparation method thereof and lithium-ion battery
By using porous Si-SiOx composites in silicon-based anode materials and covering their surface with lithium metal and amorphous carbon layer, the problems of low capacity and large volume expansion effects of silicon-based anode materials are solved, and the electrical conductivity and cyclic stability are improved.
Patent Information
- Application Number
- CN202011174357.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-10-28
AI Technical Summary
In the prior art, the capacity of the silicon-based anode material is relatively low, and the volume expansion effect is obvious during the lithium ion deintercalation process, resulting in the impact of electrochemical performance and service life.
The porous Si-SiOx composite is used as the basic material. Through the synergistic action of the lithium metal cladding layer and the amorphous carbon cladding layer, the conductive and mechanical strength of the material are improved and the volume expansion effect is reduced.
It significantly improves the conductivity and rate performance of silicon-based materials, reduces current polarization, improves the cycle stability and capacity of the battery, and reduces production costs.
Smart Images

Figure CN112382742B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-based negative electrode material, a preparation method thereof and a lithium ion battery. Background Art
[0002] Compared with traditional commonly used negative electrode materials such as graphite and lithium titanate, silicon has an absolute advantage due to its theoretical capacity of 4200mAh / g, which is especially helpful for improving the energy density of lithium-ion battery cells. However, when silicon is used as a negative electrode material, a significant volume expansion effect will occur during the process of lithium ion deintercalation, which will cause the negative electrode material to pulverize and aggravate the irreversible reaction between the negative electrode material and the electrolyte, thereby seriously affecting the electrochemical performance and service life of the lithium-ion battery. Most of the treatments for modifying silicon in the prior art include: nano-sizing micron-sized silicon powder, compounding silicon-based materials by doping and coating, or preparing materials with special three-dimensional core-shell structures based on the material structure itself. The current research hotspots focus on the following aspects: 1. Preparing silicon-based negative electrode materials with special structures by special process methods to reduce the volume expansion effect and improve the performance of the material; 2. The volume expansion of silicon oxide is smaller, and its performance and energy density are improved by doping and coating silicon oxide with carbon materials; 3. Introducing metal elements into silicon-based materials to improve the conductivity of the material. However, the above methods in the prior art have limited improvement on the capacity of silicon-based negative electrode materials. Summary of the invention
[0003] The main purpose of the present invention is to provide a silicon-based negative electrode material, a preparation method thereof and a lithium-ion battery, so as to solve the problem of low capacity of silicon-based negative electrode materials in the prior art.
[0004] In order to achieve the above object, according to one aspect of the present invention, a silicon-based negative electrode material is provided, the silicon-based negative electrode material comprising: a porous Si-SiO x Composite, wherein 0<x≤2; lithium metal coating layer, coated on porous Si-SiO x On the composite; an amorphous carbon coating layer covers the outer surface of the lithium metal coating layer.
[0005] Furthermore, the porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.017-0.035:0.008-0.035, preferably 1:0.035:0.035.
[0006] Furthermore, the thickness of the lithium metal coating layer is 100 to 300 nm, the thickness of the amorphous carbon coating layer is preferably 200 to 270 nm, and the particle size of the amorphous carbon is preferably 15 to 120 nm.
[0007] Furthermore, the porous Si-SiO x The pore size of the composite is 100-200 nm, preferably porous Si-SiO x The particle size of the composite is 8 to 30 μm.
[0008] According to another aspect of the present invention, a method for preparing the aforementioned silicon-based negative electrode material is provided, the method comprising: step S1, using lithium metal to oxidize porous Si-SiO x The composite is subjected to a pre-lithiation treatment to obtain a pre-lithiation composite; step S2, mixing the carbon source and the pre-lithiation composite and then subjecting them to a pyrolysis treatment to obtain a silicon-based negative electrode material.
[0009] Furthermore, in the above step S1, the porous Si-SiO x The mass ratio of the composite to lithium metal is 1:0.02-0.04, preferably 1:0.04, the particle size of the lithium metal is preferably 10-50 nm, and the pre-lithiation treatment is preferably selected from any one or more of chemical vapor deposition, vacuum evaporation, magnetron sputtering, and high-energy ball milling.
[0010] Furthermore, the above preparation method also includes porous Si-SiO x Preparation process of the composite: micron-sized silicon powder and magnesium metal are subjected to a first high-energy ball milling to obtain a first mixture; the first mixture is subjected to an oxidation treatment to obtain Si-SiO x / MgO composite, where 0<x≤2; using strong acid to Si-SiO x / MgO composite was etched to obtain porous Si-SiO x Composite; preferably the molar ratio of micron-sized silicon powder to magnesium metal is 1:0.05 to 0.3, the preferred oxidation treatment temperature is 600 to 1200°C, and the preferred oxidation treatment time is 5 to 12 hours.
[0011] Furthermore, the above step S2 comprises: subjecting the carbon source and the pre-lithiation composite to a second high-energy ball milling to obtain a second mixture; sintering the mixture at a temperature of 600 to 1400° C. to obtain a silicon-based negative electrode material, preferably a porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.01 to 0.04, preferably 1:0.04. The sintering is preferably carried out in an inert gas or nitrogen for 3 to 10 hours. The rotation speed of the second high-energy ball mill is preferably 150 to 800 r / min. The time of the second high-energy ball mill is preferably 12 to 60 hours. The rotation speed of the second high-energy ball mill is further preferably 150 to 450 r / min. The time of the second high-energy ball mill is preferably 12 to 18 hours.
[0012] Furthermore, the carbon source is selected from any one or more of the group consisting of soft carbon, hard carbon, artificial graphite, natural graphite, carbon nanotubes, carbon nanotube wires, and graphene.
[0013] According to another aspect of the present invention, a lithium-ion battery is provided. The lithium-ion battery includes a positive electrode and a negative electrode. The negative electrode is the aforementioned silicon-based negative electrode material.
[0014] By applying the technical solution of the present invention, since both the lithium metal coating layer and the amorphous carbon coating layer have excellent electrical conductivity, the silicon-based negative electrode material including the lithium metal coating layer and the amorphous carbon coating layer in the present invention can significantly improve the electrical conductivity of the silicon-based material. In addition, since the SEI film formed at the interface of the negative electrode consumes the lithium ions deintercalated from the positive electrode during the formation of the lithium-ion full battery, thereby reducing the capacity of the battery, the lithium metal coating layer coated on the surface of the silicon-based negative electrode material can serve as a source of lithium ions consumed by the SEI film, thereby avoiding the waste of lithium ions deintercalated from the positive electrode in the formation process, and further improving the initial efficiency and capacity of the lithium-ion full battery. On this basis, a loose and porous amorphous carbon coating is coated on the outer surface of the lithium metal coating. Since the surface of the amorphous carbon coating has abundant functional groups such as carboxyl, carbonyl, and hydroxyl, it has a large number of active sites, so that it can be more firmly combined with the lithium ions on part of the lithium metal coating. Through the intermolecular force, the lithium metal coating and the amorphous carbon coating are in closer contact, thereby obtaining a dense, porous amorphous carbon coating with certain mechanical strength. The amorphous carbon coating can effectively mitigate the huge volume expansion effect of silicon-based materials during the process of lithium insertion and extraction, and can also avoid direct contact between silicon-based materials and electrolytes, thereby ensuring the structural integrity of the electrode material and improving the cycle stability of the battery. It can be seen that through the synergistic effect of the above-mentioned lithium metal coating layer and the amorphous carbon coating layer, the obtained silicon-based negative electrode material can not only significantly improve the conductivity of the silicon-based material, reduce the polarization of the current and improve the rate performance of the battery, but also effectively mitigate the volume expansion effect of the silicon-based material and improve the cycle stability of the battery. The raw material source of the above-mentioned silicon-based negative electrode material of the present application is wide and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0016] Figure 1 A SEM image of a silicon-based negative electrode material provided according to Example 1 of the present invention is shown;
[0017] Figure 2 A SEM image of a silicon-based negative electrode material provided according to Comparative Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0019] As analyzed in the background technology, the prior art has the problem of low capacity of silicon-based negative electrode materials. To solve this problem, the present invention provides a silicon-based negative electrode material, a preparation method thereof and a lithium-ion battery.
[0020] In a typical embodiment of the present application, a silicon-based negative electrode material is provided, wherein the silicon-based negative electrode material comprises a porous Si-SiO x Composite, lithium metal coating layer and amorphous carbon coating layer, wherein 0<x≤2; lithium metal coating layer is coated on porous Si-SiO x On the composite; the amorphous carbon coating layer covers the outer surface of the lithium metal coating layer.
[0021] Since both the lithium metal coating layer and the amorphous carbon coating layer have excellent electrical conductivity, the silicon-based negative electrode material including the lithium metal coating layer and the amorphous carbon coating layer in the present invention can significantly improve the electrical conductivity of the silicon-based material. In addition, during the formation of the lithium-ion full battery, the SEI film formed at the interface of the negative electrode consumes the lithium ions deintercalated from the positive electrode, thereby reducing the capacity of the battery, and the lithium metal coating layer coated on the surface of the silicon-based negative electrode material can serve as a source of lithium ions consumed by the SEI film, thereby avoiding the waste of lithium ions deintercalated from the positive electrode in the formation process, and further improving the initial efficiency and capacity of the lithium-ion full battery. On this basis, a loose and porous amorphous carbon coating is coated on the outer surface of the lithium metal coating. Since the surface of the amorphous carbon coating has abundant functional groups such as carboxyl, carbonyl, and hydroxyl, it has a large number of active sites, so that it can be more firmly combined with the lithium ions on part of the lithium metal coating. Through the intermolecular force, the lithium metal coating and the amorphous carbon coating are in closer contact, thereby obtaining a dense, porous amorphous carbon coating with certain mechanical strength. The amorphous carbon coating can effectively mitigate the huge volume expansion effect of silicon-based materials during the process of lithium insertion and extraction, and can also avoid direct contact between silicon-based materials and electrolytes, thereby ensuring the structural integrity of the electrode material and improving the cycle stability of the battery. It can be seen that through the synergistic effect of the above-mentioned lithium metal coating layer and the amorphous carbon coating layer, the obtained silicon-based negative electrode material can not only significantly improve the conductivity of the silicon-based material, reduce the polarization of the current and improve the rate performance of the battery, but also effectively mitigate the volume expansion effect of the silicon-based material and improve the cycle stability of the battery. The raw material source of the above-mentioned silicon-based negative electrode material of the present application is wide and the production cost is low.
[0022] In order to improve the synergistic effect of the lithium metal coating layer and the amorphous carbon coating layer, the porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.017-0.035:0.008-0.035, preferably 1:0.035:0.035.
[0023] In one embodiment of the present application, the thickness of the lithium metal coating layer is 100-300 nm, the thickness of the amorphous carbon coating layer is preferably 200-270 nm, and the particle size of the amorphous carbon is preferably 15-120 nm.
[0024] The lithium metal coating layer and the amorphous carbon coating layer of the above thickness can minimize the use of lithium metal and carbon source while ensuring that the silicon-based negative electrode material has excellent conductivity, high capacity, cycle stability, mechanical strength and rate capability, thereby reducing production costs.
[0025] In one embodiment of the present application, the porous Si-SiO x The pore size of the composite is 100-200 nm, preferably porous Si-SiO x The particle size of the composite is 8 to 30 μm.
[0026] The porous Si-SiO x The pore size and particle size of the composite are more conducive to its adsorption with lithium metal, thereby better controlling the content of the lithium metal coating layer.
[0027] In another typical embodiment of the present application, a method for preparing the above-mentioned silicon-based negative electrode material is provided, the preparation method comprising step S1, using lithium metal to oxidize porous Si-SiO x The composite is subjected to a pre-lithiation treatment to obtain a pre-lithiation composite; step S2, mixing the carbon source and the pre-lithiation composite and then subjecting them to a pyrolysis treatment to obtain a silicon-based negative electrode material.
[0028] Lithium metal was used to coat porous Si-SiO x During the pre-lithiation treatment of the composite, due to the porous Si-SiO x The composite has abundant pores, which can be adsorbed on the porous Si-SiO x The composite supports a large amount of lithium metal and is simultaneously xA pre-lithiation composite with a lithium metal coating layer is formed on the surface of the composite, and then the carbon source and the pre-lithiation composite are pyrolyzed to obtain a silicon-based negative electrode material. Since both the lithium metal coating layer and the amorphous carbon coating layer have excellent electrical conductivity, the silicon-based negative electrode material including the lithium metal coating layer and the amorphous carbon coating layer in the present invention can significantly improve the electrical conductivity of the silicon-based material. In addition, during the formation of a lithium-ion full battery, the SEI film formed on the interface of the negative electrode consumes the lithium ions deintercalated from the positive electrode, thereby reducing the capacity of the battery, and the lithium metal coating layer coated on the surface of the silicon-based negative electrode material can serve as a source of lithium ions consumed by the SEI film, thereby avoiding the waste of lithium ions deintercalated from the positive electrode in the formation process, and further improving the initial efficiency and capacity of the lithium-ion full battery. On this basis, a loose and porous amorphous carbon coating is coated on the outer surface of the lithium metal coating. Since the surface of the amorphous carbon coating has abundant functional groups such as carboxyl, carbonyl, and hydroxyl, it has a large number of active sites, so that it can be more firmly combined with some lithium ions on the lithium metal coating, which not only achieves better bonding between the pre-lithiation complex and the carbon source material, but also eliminates the hanging parts on the carbon source material, and plays a buffering role on the volume expansion of the silicon-based material, thereby obtaining a dense, porous amorphous carbon coating with certain mechanical strength. The amorphous carbon coating can not only effectively mitigate the huge volume expansion effect of the silicon-based material during the lithium extraction process, but also avoid direct contact between the silicon-based material and the electrolyte, thereby ensuring the structural integrity of the electrode material and improving the cycle stability of the battery. It can be seen that through the synergistic effect of the above-mentioned lithium metal coating layer and the amorphous carbon coating layer, the obtained silicon-based negative electrode material can not only significantly improve the conductivity of the silicon-based material, reduce the polarization of the current and improve the rate performance of the battery, but also effectively mitigate the volume expansion effect of the silicon-based material and improve the cycle stability of the battery. The raw material source of the above-mentioned silicon-based negative electrode material of the present application is wide and the production cost is low.
[0029] In one embodiment of the present application, in the above step S1, the porous Si-SiO x The mass ratio of the composite to lithium metal is 1:0.02-0.04, preferably 1:0.04, the particle size of the lithium metal is preferably 10-50 nm, and the pre-lithiation treatment is preferably selected from any one or more of chemical vapor deposition, vacuum evaporation, magnetron sputtering, and high-energy ball milling.
[0030] Lithium metal in the above particle size range is more easily adsorbed into porous Si-SiO x The pores of the composite are not adsorbed by carbon, thus x A lithium metal coating layer is formed on the surface of the composite. x The composite with lithium metal helps to ensure the formation of lithium metal on porous Si-SiO xThe coating of the composite, and the above specific pre-lithiation treatment method is conducive to better forming a layered lithium metal coating layer.
[0031] In one embodiment of the present application, the above preparation method further comprises: x Preparation process of the composite: micron-sized silicon powder and magnesium metal are subjected to a first high-energy ball milling to obtain a first mixture; the first mixture is subjected to an oxidation treatment to obtain Si-SiO x / MgO composite, where 0<x≤2; using strong acid to Si-SiO x / MgO composite was etched to obtain porous Si-SiO x Composite; preferably the molar ratio of micron-sized silicon powder to magnesium metal is 1:0.05 to 0.3, the preferred oxidation treatment temperature is 600 to 1200°C, and the preferred oxidation treatment time is 5 to 12 hours.
[0032] The first ball milling is advantageous for obtaining a first mixture in which magnesium metal is uniformly dispersed in micron-sized silicon powder, so that after the first mixture is oxidized and etched, a porous Si-SiO2 with as uniform pores as possible is obtained. x composite, thus facilitating the formation of porous Si-SiO x The formation of lithium metal coating layer on the composite. The control of the molar ratio of micron-sized silicon powder to magnesium metal is beneficial to the final Si-SiO x The control of the temperature and time of the oxidation treatment helps to disperse the Si-SiO x / Mg in the mixture is oxidized to MgO to obtain Si-SiO x / MgO composite, so that after etching (removing MgO) the Si-SiO x The composite has as many pores as possible. In order to improve the etching effect of the strong acid, the strong acid is preferably selected from any one or more of hydrochloric acid, sulfuric acid, and nitric acid. In order to improve the effect of the above-mentioned oxidation treatment, it is preferred that the product after the first mixture is passed through a 300-mesh sieve is placed in a tubular furnace and oxidized in an oxygen atmosphere. In order to further improve the efficiency of the above-mentioned first high-energy ball milling, it is preferred that the rotation speed of the first high-energy ball milling is 150 to 800 r / min, and the time of the first high-energy ball milling is preferably 12 to 60 hours. It is further preferred that the rotation speed of the first high-energy ball milling is 150 to 450 r / min, and the time of the first high-energy ball milling is preferably 12 to 18 hours.
[0033] In order to enhance the interaction between the carbon source and the pre-lithiation composite, and to coat the pre-lithiation composite with a carbon coating layer, the above step S2 preferably includes subjecting the carbon source and the pre-lithiation composite to a second high-energy ball milling to obtain a second mixture; and sintering the mixture at a temperature of 600 to 1400° C. to obtain a silicon-based negative electrode material, preferably a porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.01 to 0.04, preferably 1:0.04, preferably sintered in an inert gas or nitrogen for 3 to 10 hours, preferably the second high-energy ball milling speed is 150 to 800 r / min, preferably the second high-energy ball milling time is 12 to 60 hours, more preferably the second high-energy ball milling speed is 150 to 450 r / min, preferably the second high-energy ball milling time is 12 to 18 hours. The inert gas or nitrogen, the sintering conditions of the temperature and the second high-energy ball milling conditions are all helpful to make the formed carbon coating layer as uniform and dense as possible.
[0034] In one embodiment of the present application, the carbon source is selected from any one or more of the group consisting of soft carbon, hard carbon, artificial graphite, natural graphite, carbon nanotubes, carbon nanotube wires, and graphene.
[0035] The above-mentioned carbon source is conducive to forming a carbon coating layer and reducing production costs.
[0036] In another typical embodiment of the present application, a lithium-ion battery is provided. The lithium-ion battery includes a positive electrode and a negative electrode, and the negative electrode is the aforementioned silicon-based negative electrode material.
[0037] Using the above-mentioned lithium-ion battery negative electrode material as the negative electrode of the lithium-ion battery can significantly increase the theoretical capacity of the lithium-ion battery and improve the rate performance and cycle performance of the lithium-ion battery.
[0038] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0039] Example 1
[0040] The micron-sized silicon powder and magnesium powder were subjected to the first high-energy ball milling at a molar ratio of 1:0.15, and the ball milling speed was 400r / min for 15h, and the ball milled product was passed through a 300-mesh sieve. Then, the ball milled product was placed in a tube furnace and treated at a high temperature of 1000℃ for 8h in an oxygen atmosphere to obtain Si-SiO x / MgO (0<x≤2) complex. Etching Si-SiO with HCl x / MgO, remove MgO in the composite to obtain a porous composite Si / SiO x , the porous Si-SiO x The pore size of the composite is 150 nm and the particle size is 20 μm.
[0041] According to porous Si-SiO x The mass ratio of the composite to lithium metal (particle size 30 nm) is 1:0.04. x The mass ratio of the composite to natural graphite (particle size 50 nm) is 1:0.04. x The composite and lithium powder were deposited on the porous composite Si-SiO x A layer of metallic lithium is deposited on the surface of the silicon-based negative electrode material, which is pre-lithiated to obtain a pre-lithiated composite. The pre-lithiated composite is subjected to a second high-energy ball milling with natural graphite, and then the composite is placed in a tube furnace after being ball milled at a speed of 400 r / min for 12 hours. The composite is sintered at 1200° C. for 6 hours in a nitrogen atmosphere to obtain a silicon-based negative electrode material having an amorphous carbon coating layer on the outer surface of the lithium metal coating layer. The SEM image of the silicon-based negative electrode material is shown in FIG. Figure 1 As shown. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.035, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 250 nm.
[0042] Example 2
[0043] The difference between Example 2 and Example 1 is that:
[0044] Porous Si-SiO x The mass ratio of the composite to lithium metal is 1:0.02, and finally a silicon-based negative electrode material is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.017:0.035, the thickness of the lithium metal coating layer is 100 nm, and the thickness of the amorphous carbon coating layer is 270 nm.
[0045] Example 3
[0046] The difference between Example 3 and Example 1 is that:
[0047] Porous Si-SiO x The mass ratio of the composite to lithium metal is 1:0.03, and finally a silicon-based negative electrode material is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.025:0.035, the thickness of the lithium metal coating layer is 200 nm, and the thickness of the amorphous carbon coating layer is 240 nm.
[0048] Example 4
[0049] The difference between Example 4 and Example 1 is that,
[0050] Porous Si-SiO x The mass ratio of the composite to lithium metal is 1:0.015, and a silicon-based negative electrode material is finally obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.010:0.035, the thickness of the lithium metal coating layer is 80 nm, and the thickness of the amorphous carbon coating layer is 260 nm.
[0051] Example 5
[0052] The difference between Example 5 and Example 1 is that
[0053] The particle size of lithium metal is 10nm, and finally a silicon-based negative electrode material is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.034:0.035, the thickness of the lithium metal coating layer is 290 nm, and the thickness of the amorphous carbon coating layer is 255 nm.
[0054] Example 6
[0055] The difference between Example 6 and Example 1 is that
[0056] The particle size of lithium metal is 50nm, and finally a silicon-based negative electrode material is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.030:0.035, the thickness of the lithium metal coating layer is 280 nm, and the thickness of the amorphous carbon coating layer is 260 nm.
[0057] Example 7
[0058] The difference between Example 7 and Example 1 is that
[0059] The particle size of lithium metal is 8nm, and finally a silicon-based negative electrode material is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.036:0.035, the thickness of the lithium metal coating layer is 301 nm, and the thickness of the amorphous carbon coating layer is 240 nm.
[0060] Example 8
[0061] The difference between Example 8 and Example 1 is that,
[0062] The porous Si / SiO composite was deposited by vapor deposition. x (0<x≤2) to deposit metallic lithium on the surface, and finally obtain a pre-lithiation composite. The porous Si-SiO xThe mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.034:0.035, the thickness of the lithium metal coating layer is 295 nm, and the thickness of the amorphous carbon coating layer is 250 nm.
[0063] Example 9
[0064] The difference between Example 9 and Example 1 is that
[0065] The molar ratio of micron-sized silicon powder to magnesium metal is 1:0.05, and the porous composite Si / SiO x , porous Si-SiO x The pore size of the composite is 100 nm. x The particle size of the composite is 8 μm. Finally, a pre-lithiation composite is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.038:0.035, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 250 nm.
[0066] Example 10
[0067] The difference between Example 10 and Example 1 is that
[0068] The molar ratio of micron-sized silicon powder to magnesium metal is 1:0.3, and the porous composite Si / SiO x , porous Si-SiO x The pore size of the composite is 200 nm. x The particle size of the composite is 30 μm. Finally, a pre-lithiation composite is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.031:0.035, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 250 nm.
[0069] Embodiment 11
[0070] The difference between Example 11 and Example 1 is that
[0071] The molar ratio of micron-sized silicon powder to magnesium metal is 1:0.03, and the porous composite Si / SiO x , porous Si-SiO x The pore size of the composite is 220 nm. x The particle size of the composite is 35 μm. Finally, a pre-lithiation composite is obtained. The porous Si-SiO xThe mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.025:0.035, the thickness of the lithium metal coating layer is 250 nm, and the thickness of the amorphous carbon coating layer is 270 nm.
[0072] Example 12
[0073] The difference between Example 12 and Example 1 is that
[0074] The oxidation temperature was 600 °C and the oxidation time was 12 h to obtain a porous composite Si / SiO x , porous Si-SiO x The pore size of the composite is 160 nm. x The particle size of the composite is 20 μm. Finally, a pre-lithiation composite is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.028:0.035, the thickness of the lithium metal coating layer is 250 nm, and the thickness of the amorphous carbon coating layer is 270 nm.
[0075] Embodiment 13
[0076] The difference between Example 13 and Example 1 is that
[0077] The oxidation temperature was 580 °C and the oxidation time was 12 h to obtain a porous composite Si / SiO x , porous Si-SiO x The pore size of the composite is 165 nm. x The particle size of the composite is 20 μm. Finally, a pre-lithiation composite is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.025:0.035, the thickness of the lithium metal coating layer is 245 nm, and the thickness of the amorphous carbon coating layer is 270 nm.
[0078] Embodiment 14
[0079] The difference between Example 14 and Example 1 is that
[0080] The oxidation treatment temperature is 1200°C, and the oxidation treatment time is preferably 5 hours to obtain a porous composite Si / SiO x , porous Si-SiO x The pore size of the composite is 105 nm, and the porous Si-SiO x The particle size of the composite is 20 μm. Finally, a pre-lithiation composite is obtained. The porous Si-SiO xThe mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.038:0.035, the thickness of the lithium metal coating layer is 280 nm, and the thickness of the amorphous carbon coating layer is 200 nm.
[0081] Embodiment 15
[0082] The difference between Example 15 and Example 1 is that
[0083] Porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.01, and a silicon-based negative electrode material is finally obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.008, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 200 nm.
[0084] Example 16
[0085] The difference between Example 16 and Example 1 is that
[0086] Porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.03, and a silicon-based negative electrode material is finally obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.028, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 260 nm.
[0087] Embodiment 17
[0088] The difference between Example 17 and Example 1 is that
[0089] Porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.05, and a silicon-based negative electrode material is finally obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.04, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 280 nm.
[0090] Embodiment 18
[0091] The difference between Example 18 and Example 1 is that
[0092] The second high-energy ball milling speed was 450r / min, and the second high-energy ball milling time was 12h, and finally a silicon-based negative electrode material was obtained. xThe mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.038, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 270 nm.
[0093] Embodiment 19
[0094] The difference between Example 19 and Example 1 is that
[0095] The second high-energy ball milling speed was 150 r / min, and the second high-energy ball milling time was 18 h. Finally, a silicon-based negative electrode material was obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.036, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 260 nm.
[0096] Embodiment 20
[0097] The difference between Example 20 and Example 1 is that
[0098] The second high-energy ball milling speed was 800 r / min, and the second high-energy ball milling time was 12 h, and finally a silicon-based negative electrode material was obtained. x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.034, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 250 nm.
[0099] Embodiment 21
[0100] The difference between Example 21 and Example 1 is that
[0101] The second high-energy ball milling speed was 100 r / min, and the second high-energy ball milling time was 12 h, and finally a silicon-based negative electrode material was obtained. x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.030, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 240 nm.
[0102] Embodiment 22
[0103] The difference between Example 22 and Example 1 is that
[0104] The sintering temperature is 600℃ and the sintering time is 10h, and finally a silicon-based negative electrode material is obtained. xThe mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.037, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 260 nm.
[0105] Embodiment 23
[0106] The difference between Example 23 and Example 1 is that
[0107] The sintering temperature is 1400℃ and the sintering time is 3h, and finally a silicon-based negative electrode material is obtained. x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.038, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 270 nm.
[0108] Embodiment 24
[0109] The difference between Example 24 and Example 1 is that
[0110] The sintering temperature is 580℃ and the sintering time is 10h, and finally a silicon-based negative electrode material is obtained. The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.032, the thickness of the lithium metal coating layer is 300 nm, and the thickness of the amorphous carbon coating layer is 200 nm.
[0111] Comparative Example 1
[0112] The difference between Comparative Example 1 and Example 1 is that only in the porous Si-SiO x The surface of the composite is coated with a lithium metal coating layer to obtain a silicon-based negative electrode material. The SEM image of the silicon-based negative electrode material is as follows: Figure 2 shown.
[0113] Comparative Example 2
[0114] The difference between Comparative Example 2 and Example 1 is that only in the porous Si-SiO x The surface of the composite is coated with an amorphous carbon coating layer to obtain a silicon-based negative electrode material.
[0115] The average particle sizes of the silicon-based negative electrode materials of Examples 1 to 24, Comparative Example 1 and Comparative Example 2 were tested using a laser particle size analyzer, and the test results are listed in Table 1.
[0116] Preparation of button lithium-ion battery:
[0117] The silicon-based negative electrode materials prepared in the above Examples 1 to 24, Comparative Example 1 and Comparative Example 2 were used as negative electrodes, NCM811 ternary was used as positive electrodes, and separators and electrolytes were added to prepare button-type lithium-ion batteries 1 to 26. The initial lithium insertion specific capacity, initial lithium removal specific capacity, and capacity retention rate of 0.5C cycles for 100 cycles of the button-type lithium-ion batteries 1 to 26 were tested, and the results are listed in Table 2. The rate properties of the button-type lithium-ion batteries 1 to 26 at 0.5C, 1C, 2C, and 3C were tested, and the results are listed in Table 3.
[0118] Table 1
[0119]
[0120]
[0121] Table 2
[0122]
[0123]
[0124] Table 3
[0125]
[0126]
[0127] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0128] Since both the lithium metal coating layer and the amorphous carbon coating layer have excellent electrical conductivity, the silicon-based negative electrode material including the lithium metal coating layer and the amorphous carbon coating layer in the present invention can significantly improve the electrical conductivity of the silicon-based material. In addition, during the formation of the lithium-ion full battery, the SEI film formed at the interface of the negative electrode consumes the lithium ions deintercalated from the positive electrode, thereby reducing the capacity of the battery, and the lithium metal coating layer coated on the surface of the silicon-based negative electrode material can serve as a source of lithium ions consumed by the SEI film, thereby avoiding the waste of lithium ions deintercalated from the positive electrode in the formation process, and further improving the initial efficiency and capacity of the lithium-ion full battery. On this basis, a loose and porous amorphous carbon coating is coated on the outer surface of the lithium metal coating. Since the surface of the amorphous carbon coating has abundant functional groups such as carboxyl, carbonyl, and hydroxyl, it has a large number of active sites, so that it can be more firmly combined with the lithium ions on part of the lithium metal coating. Through the intermolecular force, the lithium metal coating and the amorphous carbon coating are in closer contact, thereby obtaining a dense, porous amorphous carbon coating with certain mechanical strength. The amorphous carbon coating can effectively mitigate the huge volume expansion effect of silicon-based materials during the process of lithium insertion and extraction, and can also avoid direct contact between silicon-based materials and electrolytes, thereby ensuring the structural integrity of the electrode material and improving the cycle stability of the battery. It can be seen that through the synergistic effect of the above-mentioned lithium metal coating layer and the amorphous carbon coating layer, the obtained silicon-based negative electrode material can not only significantly improve the conductivity of the silicon-based material, reduce the polarization of the current and improve the rate performance of the battery, but also effectively mitigate the volume expansion effect of the silicon-based material and improve the cycle stability of the battery. The raw material source of the above-mentioned silicon-based negative electrode material of the present application is wide and the production cost is low.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material comprises: Porous Si-SiO x Complex, where 0<x≤2; The lithium metal coating layer is coated on the porous Si-SiO x On the composite; An amorphous carbon coating layer covers the outer surface of the lithium metal coating layer.
2. The silicon-based negative electrode material according to claim 1, characterized in that: The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1: 0.017-0.035: 0.008-0.
035.
3. The silicon-based negative electrode material according to claim 2, characterized in that: The porous Si-SiO x The mass ratio of the composite, the lithium metal coating layer and the amorphous carbon coating layer is 1:0.035:0.
035.
4. The silicon-based negative electrode material according to claim 1, characterized in that: The thickness of the lithium metal coating layer is 100 to 300 nm.
5. The silicon-based negative electrode material according to claim 1, characterized in that: The thickness of the amorphous carbon coating layer is 200-270 nm.
6. The silicon-based negative electrode material according to claim 1, characterized in that: The particle size of the amorphous carbon is 15 to 120 nm.
7. The silicon-based negative electrode material according to claim 1, characterized in that: The porous Si-SiO x The pore size of the composite is 100-200 nm.
8. The silicon-based negative electrode material according to claim 1, characterized in that: The porous Si-SiO x The particle size of the composite is 8 to 30 μm.
9. The method for preparing a silicon-based negative electrode material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Step S1, using lithium metal to x The composite is subjected to a pre-lithiation treatment to obtain a pre-lithiation composite; Step S2, mixing the carbon source with the pre-lithiation composite and then performing a pyrolysis treatment to obtain the silicon-based negative electrode material.
10. The preparation method according to claim 9, characterized in that: In the step S1, the porous Si-SiO x The mass ratio of the composite to the lithium metal is 1:0.02-0.
04.
11. The preparation method according to claim 10, characterized in that: The porous Si-SiO x The mass ratio of the composite to the lithium metal is 1:0.
04.
12. The preparation method according to claim 9, characterized in that: In the step S1, the particle size of the lithium metal is 10 to 50 nm.
13. The preparation method according to claim 9, characterized in that: In the step S1, the pre-lithiation treatment is selected from any one or more of chemical vapor deposition, vacuum evaporation, magnetron sputtering, and high-energy ball milling.
14. The preparation method according to claim 9, characterized in that: The preparation method further comprises the step of x Preparation process of the complex: Performing a first high-energy ball milling on micron-sized silicon powder and magnesium metal to obtain a first mixture; The first mixture is oxidized to obtain Si-SiO x / MgO composite, wherein 0<x≤2; The Si-SiO x / MgO composite is etched to obtain the porous Si-SiO x Complex.
15. The preparation method according to claim 14, characterized in that: The molar ratio of the micron-sized silicon powder to the magnesium metal is 1:0.05-0.
3.
16. The preparation method according to claim 14, characterized in that: The temperature of the oxidation treatment is 600-1200°C.
17. The preparation method according to claim 14, characterized in that: The oxidation treatment time is 5 to 12 hours.
18. The preparation method according to claim 9, characterized in that: The step S2 comprises: Performing a second high-energy ball milling on the carbon source and the pre-lithiation complex to obtain a second mixture; The mixture is sintered at a temperature of 600 to 1400° C. to obtain the silicon-based negative electrode material.
19. The preparation method according to claim 18, characterized in that: The porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.01-0.
04.
20. The preparation method according to claim 18, characterized in that: The porous Si-SiO x The mass ratio of the composite to the carbon source is 1:0.
04.
21. The preparation method according to claim 18, characterized in that: The sintering is performed in an inert gas or nitrogen atmosphere for 3 to 10 hours.
22. The preparation method according to claim 18, characterized in that: The rotation speed of the second high energy ball mill is 150-800 r / min.
23. The preparation method according to claim 22, characterized in that: The rotation speed of the second high energy ball mill is 150-450 r / min.
24. The preparation method according to claim 18, characterized in that: The time of the second high-energy ball milling is 12 to 60 hours.
25. The preparation method according to claim 24, characterized in that: The time of the second high-energy ball milling is 12 to 18 hours.
26. The preparation method according to claim 9, characterized in that: The carbon source is selected from any one or more of the group consisting of soft carbon, hard carbon, artificial graphite, natural graphite, carbon nanotubes, carbon nanotube wires, and graphene.
27. A lithium ion battery, comprising a positive electrode and a negative electrode, characterized in that: The negative electrode is the silicon-based negative electrode material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Composite silicon based electrode material, preparation method and application thereof
CN107394161A
Lithium-supplementing porous silicon monoxide negative electrode material for lithium ion batteries and preparation method thereof
CN109309220A